Identification of 18 vector species belonging to Group I, Group II, and Group III 'Dirty 22' species known to contaminate food and spread foodborne pathogens: DNA barcoding study of public health importance. (12th December 2016) - Sulaiman, Irshad M.; Jacobs, Emily; Simpson, Steven; Kerdahi, Khalil
Abstract: The US Food and Drug Administration (US-FDA) uses the presence of filth and extraneous materials as one of the criteria in implementing regulatory actions and assessing food adulteration of public health importance. So far, 22 common pest species ('Dirty 22' species) have been considered by this agency for the spreading of foodborne illness, and their presence is an indicator of unsanitary conditions in food processing and storage facilities. Recently, we classified the 'Dirty 22' species into four groups: Group I (four cockroach species), Group II (two ant species), Group III (12 fly species), and Group IV (four rodent species), and described two molecular diagnostic methods for group-specific identification. We developed a PCR-RFLP assay based on rRNA gene for the detection and differentiation of Group I 'Dirty 22' species. Later, we designed three Group II 'Dirty 22' species-specific nested PCR primer sets and sequence characterized the rRNA, elongation factor 1-alpha (EF-1a), and wingless (WNT-1) loci. In this follow-up study, we have evaluated the robustness of five unique sets of published primers targeting the mitochondrial cytochrome oxidase I (COI) gene for insect barcoding. With modified PCR conditions, we successfully used COI barcoding for 18 members of Group I, Group II, and Group III 'Dirty 22' species. Results of this study reveal that COI barcoding is an effective tool for rapid identification of insects of Groups I, II, and III 'Dirty 22' species known to contaminate food and spread foodborne pathogens.